Quaternary equatorial Atlantic deep-sea ostracodes: evidence for a distinct tropical fauna in the deep sea. (December 2021) - Yasuhara, Moriaki; Okahashi, Hisayo; Huang, Huai-Hsuan May; Hong, Yuanyuan; Iwatani, Hokuto; Chu, Rachel Wai Ching; Hunt, Gene
Abstract: Low-latitude, deep-sea faunas remain poorly understood and described. Here, we systematically describe Quaternary deep-sea ostracodes from the Ocean Drilling Program (ODP) Site 925 (Ceara Rise; 4°12.2'N, 43°29.3′W; 3040 m water depth) in the equatorial Atlantic Ocean. Twenty-six genera and 52 species were examined and illustrated with high-resolution scanning electron microscopy images. Six new species are described herein: Pseudocythere spinae, Hemiparacytheridea zarikiani, Pedicythere canis, Xylocythere denticulata, Paracytherois obtusa, and Poseidonamicus sculptus . The results show that deep-sea ostracodes have a tropical faunal element that is distinctive from higher latitude ostracodes, and that is globally distributed in low latitudes. This tropical faunal component is possibly a Tethyan legacy of a fauna that was widely distributed in tropical and extratropical latitudes in deep waters during greenhouse conditions in the Cretaceous and early Cenozoic. Global cooling thereafter shrank its distribution, limiting it to tropical latitudes, perhaps with the relatively warm uppermost bathyal area acting as the source or refuge of this faunal component. Because similar present-day biogeographic patterns (i.e., presence and wide distribution of tropical deep-sea fauna) are known in other deep-sea benthic groups, this scenario might be applicable to the deep-sea benthos more broadly. UUID: http://zoobank.org/552d4cb2-c0db-463a-ae3f-b2efcc0985df .